Implementation of the Exploratory Discovery Approach to Enhance Student Creativity in Islamic Religious Education - Samsudin, Arif; Fihris, Fihris; Chamami, M. Rikza; Muthohar, Sofa; Rohman, Rohman (Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (PAI) learning in senior high schools still tends to be teacher-centered, resulting in limited development of students’ active participation, creativity, and independent learning. This condition highlights the need for a learning approach that encourages exploration, concept discovery, and active student engagement. The Exploratory Discovery approach is considered relevant as it emphasizes independent exploration, group discussion, concept discovery, and reflection, which align with constructivist principles and 21st-century competencies. This study aims to describe the implementation of the Exploratory Discovery approach in PAI learning for grade XI students at SMA Negeri 03 Semarang and to analyze the forms of student creativity as well as the supporting and inhibiting factors affecting its effectiveness. This research employed a descriptive qualitative method with purposive sampling involving three PAI teachers and five grade XI students. Data were collected through participatory observation, semi-structured interviews, and documentation, including lesson plans, syllabi, and students’ work. Data analysis followed the Miles and Huberman model through data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that the implementation of the Exploratory Discovery approach enhances students’ creativity in the form of mind maps, posters, miniatures, and critical argumentation skills. Supporting factors include a conducive learning environment and the teacher’s role as a facilitator, while inhibiting factors include differences in student readiness, limited instructional time, and initial dependence on the teacher.